Calculation of the reinforced design of road clothes as multilayered plate on the elastic basis - S. A. Matveev; E. A. Martynov; N. N. Litvinov (Вестник СибАДИ, 2017)
In article the settlement model of the reinforced crushed-stone-sand basis of road clothes with the variable module of elasticity changing on layer depth on exponential dependence is offered. The settlement model is based on representation of the reinforced layer of granular material as the multilayered plate consisting of any quantity of the continuous layers which are rigidly linked among themselves. The method of calculation of the reinforced bases of road clothes leaning on experimental data is offered. A concrete example of calculation is reviewed.